Using TikTok for English Language Learning in Indonesian Formal Education: A Systematic Literature Review - Ahen, Christina Novita Apriliana Pascha; Ikhsanudin, Ikhsanudin; Rosnija, Eni (Journal of Language and Literature Studies, 2025)
This study aims to synthesize findings on the uses, benefits, and challenges of using TikTok for English language learning in the Indonesian formal education context through a systematic literature review. Following the PRISMA guidelines, relevant studies published between 2021-2025 were systematically retrieved from Google Scholar and SINTA. Studies were screened by title and abstract, and full texts were assessed for eligibility. In total, 39 articles met the criteria for review. The review found that TikTok was frequently used as a source of learning materials, a medium for creating learner-generated videos, and a reference for tasks. The use of features such as duet and save facilitated interaction, engagement, and review. Key benefits included improvements in speaking, vocabulary, motivation, confidence, and a more enjoyable learning environment, along with other reported benefits related to the skills and engagement outcomes. However, challenges included distractions from entertainment content, difficulties with features, irrelevant or low-quality content, limited internet access, and video creation difficulties, in addition to other less frequent technical and pedagogical issues. Despite challenges, these highlight the importance of content quality, effective facilitation, and purposeful platform integration to ensure meaningful and engaging learning experiences. Therefore, these findings provide practical implications for the management and integration of TikTok in English language learning within Indonesia’s formal education system.